Decoding mpox: a systematic review and meta-analysis of the transmission and severity parameters of the 2022–2023 global outbreak - Adriana Buitrago-Lopez; Zulma M Cucunubá; Candida Diaz Brochero; Laura Cristina Nocua-Báez; Jorge Alberto Cortes; Kelly Charniga (BMJ Global Health)
Introduction The 2022–2023 mpox outbreak has been the largest in history. We aim to synthesise the key epidemiological parameters related to the dynamics, transmission, and severity of mpox (incubation period, serial interval, generation time, infectious period, basic (R0) and effective (R(t)) reproductive number, and case fatality rate (CFR)).Methods Systematic review of observational studies in MEDLINE, EMBASE and other sources up to September 2023 (PROSPERO: CRD42023404503). Quality assessment using the Joanna Briggs Institute Critical Appraisal for case series, cross-sectional and cohort studies, and a designed quality assessment questionnaire for mathematical models. Meta-analysis was performed using a random effects model.Results For transmissibility parameters, we estimated a pooled incubation period of 7.60 (95% CI 7.14 to 8.10) days and a pooled serial interval of 8.30 (95% CI 6.74 to 10.23) days. One study reported a generation time of 12.5 days (95% CI 7.5 to 17.3). Three studies reported presymptomatic transmission in 27–50% of paired cases investigated. R(t) varied between 1.16 and 3.74 and R0 varied between 0.006 and 7.84. The epidemic peaked between August and September 2022 in Europe and the Americas whereas transmission has continued in African countries. For severity parameters, we estimated a pooled CFR by continent: 0.19% (95% CI 0.09% to 0.37%) for the Americas and 0.33% (95% CI 0.15% to 0.7%) for Europe. For Africa, we found that the CFRs of countries associated with group I were higher (range 17–64%) than those associated with group IIb (range 0–6%).Conclusion Pooled mpox serial interval was slightly larger than pooled incubation period, suggesting transmission occurs mostly postsymptom onset, although presymptomatic transmission can occur in an important proportion of cases. CFR estimates varied by geographical region and were higher in Africa, in countries linked with clade I. Our results contribute to a better understanding of mpox dynamics, and the development of mathematical models to assess the impact of current and future interventions.